2019
DOI: 10.7759/cureus.5360
|View full text |Cite
|
Sign up to set email alerts
|

Google Search Trends in Oncology and the Impact of Celebrity Cancer Awareness

Abstract: IntroductionThere is widespread public interest when celebrities are diagnosed with cancer. We sought to assess how this interest impacts awareness of prevalent cancers.MethodsWe reviewed common cancer-related search terms using Google Trends (Google LLC, Mountain View, CA) between the years 2004 and 2017 and retrospectively correlated these findings with media or celebrity-related events. The Google Trends application was used to obtain the “search volume index” (SVI), defined as the number of searches for a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 10 publications
2
33
2
Order By: Relevance
“…Our results align with previous research that describes a comparable increase in Google search traffic related to breast cancer during Breast Cancer Awareness Month [ 7 , 23 ]. However, our findings indicate that monthly awareness campaigns for [‘Cervical Cancer’], [‘Colorectal Cancer’], [‘Skin Cancer’], [‘Ovarian Cancer’] and [‘Lung Cancer’] have also successfully increased Google search traffic, which is contrary to a previous report that found little evidence to support the effectiveness of non-breast cancer monthly awareness campaigns [ 24 ]. In contrast to the methods used in the referenced paper, our study used statistical analyses such as two-sample independent t -tests to compare GT data in awareness months versus non-awareness months, while the previous study solely identified sharp peaks in RSV from baseline and did not use any statistical tests to evaluate the relationship between monthly cancer awareness campaigns and corresponding GT search traffic.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results align with previous research that describes a comparable increase in Google search traffic related to breast cancer during Breast Cancer Awareness Month [ 7 , 23 ]. However, our findings indicate that monthly awareness campaigns for [‘Cervical Cancer’], [‘Colorectal Cancer’], [‘Skin Cancer’], [‘Ovarian Cancer’] and [‘Lung Cancer’] have also successfully increased Google search traffic, which is contrary to a previous report that found little evidence to support the effectiveness of non-breast cancer monthly awareness campaigns [ 24 ]. In contrast to the methods used in the referenced paper, our study used statistical analyses such as two-sample independent t -tests to compare GT data in awareness months versus non-awareness months, while the previous study solely identified sharp peaks in RSV from baseline and did not use any statistical tests to evaluate the relationship between monthly cancer awareness campaigns and corresponding GT search traffic.…”
Section: Discussioncontrasting
confidence: 99%
“…The five search terms with the most interest during our established time period were identified as ‘COVID Vaccine Fertility’, ‘COVID Vaccine and Infertility’, ‘COVID Vaccine Infertility’, ‘COVID Vaccine Fertility CDC’, and ‘COVID 19 Vaccine Infertility’. Interest for a given keyword was reported as Search Volume Index (SVI) calculated as the proportion of keyword searches divided by all searches in a given location and time period (Kaleem et al., 2019 ). SVI may range from 0 to 100, with 100 representing the maximum search interest at that time and location selected for a given keyword.…”
Section: Methodsmentioning
confidence: 99%
“…Goggle Trends and the field of infodemiology are being widely used in the field of health-related issues as well. Public attention in different fields of health care has been published recently (eg, osteoarthritis, breast cancer, or chronic inflammatory lung disease) [ 34 , 56 , 57 ]. Furthermore, infodemiology and Google Trends are used to generate awareness profiles and are suitable substitutes for classical data collection, such as surveys [ 50 ].…”
Section: Discussionmentioning
confidence: 99%